Proportion of Agriculture, Industry and Services Sector to Value Added Tax Revenue in Low Income and Lower-Middle Income Countries: Rule of Law as a Moderating Variable - Noya, Avior Ocean Louis Ishaac; Wijaya, Suparna; Hutagaol, Dian Thasya F (Politeknik Keuangan Negara STAN, 2023)
This study aims to determine how much the agricultural, industrial and service sectors affect Value Added Tax revenues in low and lower middle income countries with rule of law as moderating variable. The independent variables used in this study are the proportion of the agricultural sector to GDP, the proportion of the industrial sector to GDP, the proportion of the service sector to GDP, the dependent variable used is VAT revenue while the moderating variable is the rule of law. This study uses secondary data with a population of 27 countries with low and lower middle income in a span of seven years, from 2009 to 2015. The statistical method used in this study is quantitative method with multiple linear regression using panel-corrected standard error regression model. The results showed that before being moderated by the rule of law, the agricultural, industrial and service sectors had no effect on VAT revenues. But after being moderated by the rule of law, the agricultural, industrial and service sectors have a positive influence on VAT revenues. Thus, the government is expected to focus attention on the rule of law. Good rule of law will increase investor confidence in the existence of applicable laws and also related to property rights, law enforcement officers, courts and also low levels of crime and violence which ultimately increase tax revenues reflected in increased VAT revenues.